Magnetic orderings and phase separations in the zero-bandwidth limit of the extended Hubbard model with intersite magnetic interactions - Kłobus, Waldemar; Kapcia, Konrad; Robaszkiewicz, Stanisław (Polish Academy of Sciences, Institute of Physics, al. Lotników 32-46, Pl-02-668 Warsaw, Poland, 2010)
A simple effective model for a description of magnetically ordered insulators is analysed. The tight binding Hamiltonian consists of the effective on-site interaction (U) and intersite magnetic exchange interactions (Jz, Jxy) between nearest-neighbours. The phase diagrams of this model have been determined within the variational approach, which treats the on-site interaction term exactly and the intersite interactions within the mean-field approximation. We show that, depending on the values of interaction parameters and the electron concentration, the system can exhibit not only homogeneous phases: (anti-)ferromagnetic (F) and nonordered (NO), but also phase separated states (PS: F-NO).
This is an author-created, un-copyedited version of an article accepted for publication in Acta Physica Polonica A. The Version of Record is available online at http://przyrbwn.icm.edu.pl/APP/PDF/118/a118z2p31.pdf
Keywords: magnetic orderings; phase separations; extended Hubbard Model; atomic limit